Climate change mitigation: potential benefits and pitfalls of enhanced rock weathering in tropical agriculture. (5th April 2017) - Edwards, David P.; Lim, Felix; James, Rachael H.; Pearce, Christopher R.; Scholes, Julie; Freckleton, Robert P.; Beerling, David J.
Abstract : Restricting future global temperature increase to 2°C or less requires the adoption of negative emissions technologies for carbon capture and storage. We review the potential for deployment of enhanced weathering (EW), via the application of crushed reactive silicate rocks (such as basalt), on over 680 million hectares of tropical agricultural and tree plantations to offset fossil fuel CO2 emissions. Warm tropical climates and productive crops will substantially enhance weathering rates, with potential co-benefits including decreased soil acidification and increased phosphorus supply promoting higher crop yields sparing forest for conservation, and reduced cultural eutrophication. Potential pitfalls include the impacts of mining operations on deforestation, producing the energy to crush and transport silicates and the erosion of silicates into rivers and coral reefs that increases inorganic turbidity, sedimentation and pH, with unknown impacts for biodiversity. We identify nine priority research areas for untapping the potential of EW in the tropics, including effectiveness of tropical agriculture at EW for major crops in relation to particle sizes and soil types, impacts on human health, and effects on farmland, adjacent forest and stream-water biodiversity.